The effect of different irrigants on sealer penetration into dentinal tubules with and without activation, using confocal scanning microscope - Helayl A Alshaibani; Shibu Thomas Mathew (Wolters Kluwer Medknow Publications, 2022)
Purpose: To compare the effectiveness of three root canal irrigants with the influence of activation technique on the depth of sealer penetration into dentinal tubules using a confocal laser scanning microscope (CLSM). Materials and Methods: Sixty recently extracted human mandibular premolars with single straight canals (n = 60) were prepared with ProTaper Next NiTi rotary files up to X3. The samples were divided into three groups according to the final irrigation solution (n = 20), 5.25% sodium hypochlorite, 2% chlorhexidine digluconate, 17% ethylene-diamine-tetraacetic acid (EDTA). Each group was further subdivided into two groups according to the ultrasonic activation protocol and then obturated with a single gutta-percha size X3 and labeled sealer mixed with 0.01% fluorescent rhodamine B after the final irrigation protocol. Transverse sections were obtained at 2, 5, and 8 mm from the apex and observed under CLSM. It recorded the maximum penetration depth of both irrigant and sealer. Data were analyzed using a three-way analysis of variance and Tukey test (P = 0.05). Results: 17% EDTA exhibited significantly higher penetration depth with ultrasonic activation than the other groups and also determined (P < 0.011) statistically significant differences at root canal third (coronal, middle, apical; P < 0.011). Conclusions: The dentinal tubule penetration was significantly affected by selecting a root canal irrigant, an ultrasonic activation protocol, and root canal third. 17% EDTA with ultrasonic activation seemed beneficial in dentinal tubule penetration. Hence, the depth of sealer penetration might influence the outcome or success rate of endodontic therapy.